2021
DOI: 10.1016/j.asoc.2021.107592
|View full text |Cite
|
Sign up to set email alerts
|

Short-term prediction of COVID-19 spread using grey rolling model optimized by particle swarm optimization

Abstract: The prediction of the spread of coronavirus disease 2019 (COVID-19) is vital in taking preventive and control measures to reduce human health damage. The Grey Modeling (1,1) is a popular approach used to construct a predictive model with a small-sized data set. In this study, a hybrid model based on grey prediction and rolling mechanism optimized by particle swarm optimization algorithm (PSO) was applied to create short-term estimates of the total number of confirmed COVID-19 cases for three countries, Germany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Due to its excellent and stable prediction performance for small sample data, many scholars applied the grey prediction model to the prediction of COVID-19. For example, Zeynep [25] used a classical GM(1,1) model with the rolling mechanism to predict the number of confirmed cases in Germany, Turkey, and the United States. Liu et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to its excellent and stable prediction performance for small sample data, many scholars applied the grey prediction model to the prediction of COVID-19. For example, Zeynep [25] used a classical GM(1,1) model with the rolling mechanism to predict the number of confirmed cases in Germany, Turkey, and the United States. Liu et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To effectively deal with the non-linear patterns of daily reported infectious cases, there are recent attempts of Ceylan ( Ceylan, 2021 ) and Hansun et al ( Hansun et al, 2021 ) have demonstrated the effectiveness of integrating NARNN architecture. These NARRN-based models ( Ceylan, 2021 , Hansun et al, 2021 ) support to model the flexible time-dependent growth patterns of Covid-19 diseases in different real-world datasets. In general, the NARNN approach is basically considered as an initial artificial neural network based technique.…”
Section: Our Case Studies and Related Workmentioning
confidence: 99%
“…This type of infectious data is majorly influenced by different external aspects. In order to deal with the non-linear and complex sequential data pattern learning, there are several studies ( Ceylan, 2021 , Wu et al, 2015 , Yu et al, 2014 ) have applied the NARNN-based approach to enable the capability of predictive system in performing non-linear and time-series based data analysis problem. In this approach, the temporal information is efficiently preserved from the input time-dependent observations through the neural network based learning paradigm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are widely used in medicines [4][5][6][7][8][9], and other areas such as petroleum, geological engineering, industry, management, marketing, and agriculture [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In medicines and public health, the spread of diseases is affected by several uncertain factors, so the Grey theory with dynamic changes is suitable to be used.…”
mentioning
confidence: 99%